2020
DOI: 10.1177/0363546519895259
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Hip Arthroscopy in High-Level Athletes: Results of a Shorter Interval Between Staged Bilateral Hip Arthroscopies

Abstract: Background: Hip arthroscopy is a safe and effective mechanism for treating femoroacetabular impingement symptoms in high level athletes. Bilateral symptoms occur in a subset of this population. Purpose: To discuss outcomes of bilateral hip arthroscopy in high-level athletes and compare a standard staged timeline for bilateral hip arthroscopic surgery versus an accelerated timeline. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective review of all staged bilateral hip arthroscopies was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…The results of the present study suggested that the outcome of bilateral hip arthroscopy statistically behaves like a dependent event rather than an independent event. This is supported by the findings of Hassebrock et al, 31 who compared PROs among 133 patients undergoing bilateral hip arthroscopy and found similar outcomes between surgical sides.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The results of the present study suggested that the outcome of bilateral hip arthroscopy statistically behaves like a dependent event rather than an independent event. This is supported by the findings of Hassebrock et al, 31 who compared PROs among 133 patients undergoing bilateral hip arthroscopy and found similar outcomes between surgical sides.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, the interval between the first and second hip arthroscopy was not standardized in this study, and no conclusions were able to be made regarding the timing of a staged procedure, which has been a recent topic of interest. 31 Last, the present study was based on minimum 2-year follow-up, but longer follow-up is necessary to determine the durability of the results.…”
Section: Limitationsmentioning
confidence: 99%
“…1,6,7,30 It is well recognized that 15% to 40% of patients presenting with unilateral symptoms who have undergone primary arthroscopic surgery for FAIS will need bilateral surgery, as the contralateral hip later becomes symptomatic. 16,26-28,34 Furthermore, symptomatic FAIS occurring bilaterally has been increasingly recognized in the recently published literature. 1,12,17,21 This trend has been more apparent in the adolescent population, especially those involved in athletics who present with large cam lesions.…”
mentioning
confidence: 99%
“…16 Prospective studies of arthroscopic treatment for FAI have shown stable functional improvement postoperatively. 11,13,31 When compared with nonoperative management, arthroscopic intervention produces clinically meaningful improvements in function, with few associated side effects and minimal progression to osteoarthritis. 12,27…”
mentioning
confidence: 99%
“…16 Prospective studies of arthroscopic treatment for FAI have shown stable functional improvement postoperatively. 11,13,31 When compared with nonoperative management, arthroscopic intervention produces clinically meaningful improvements in function, with few associated side effects and minimal progression to osteoarthritis. 12,27 Despite continued efforts to standardize the diagnosis of FAI, it remains challenging to definitively determine the contribution of intra-articular pathology to patients' symptoms.…”
mentioning
confidence: 99%